Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 2536 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Actias Leach, 1815" ] } The dataset includes 2536 records from 48 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0005599-150922153815467/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences